MicroRNA-21 Contributes to Acute Liver Injury in LPS-Induced Sepsis Mice by Inhibiting PPARα Expression - Xianjin Du; Miao Wu; Dan Tian; Jianlin Zhou; Lu Wang; Liying Zhan (PPAR Research)
The severity of sepsis may be associated with excessive inflammation, thus leading to acute liver injury. MicroRNA-21 is highly expressed in the liver of a variety of inflammation-related diseases, and PPARα is also proved to participate in regulating inflammation. In the present study, the LPS-induced sepsis model was established. We found that microRNA-21 expression was upregulated in the liver of sepsis mice, and microRNA-21 inhibition significantly reduced the liver injury. The expression of liver injury markers, inflammation cytokines, and PPARα in the septic mice was higher than in antagomir-21 treated septic mice. In addition, we also found that PPARα is the target gene of microRNA-21; PPARα antagonist GW6471 could reverse the effect of antagomir-21. In conclusion, our study illustrated that microRNA-21 exacerbate acute liver injury in sepsis mice by inhibiting PPARα expression.